The Governance of Sports Organizations in Morocco: the Case of the Royal Moroccan Federation of Judo and Related Martial Arts - Hannoun, Omar (International Journal of Engineering and Management Sciences, 2024)
Governance is crucial for effective sports organization management, particularly as sports organizations increasingly adopt business models. Research inquiries into suitable governance practices in sports have grown, reflecting the evolving landscape of sports management. This qualitative research examined the governance of the Moroccan Judo Federation through semi-structured interviews and analysis using Voyant Tools. Stakeholders, including the vice president, board members, coaches, athletes, referees, technical committee members, and financial manager, provided insights on key aspects of governance. The findings emphasized the importance of strong leadership, effective decision-making processes, transparent governance structures, stakeholder engagement, and ethical conduct. However, challenges were identified in decision-making, stakeholder engagement, conflict resolution, and financial management. Stakeholders highlighted the need for inclusive decision-making processes and transparent and accountable governance practices. By addressing these challenges, the federation can strengthen its governance, support judo’s growth, and foster fairness and inclusivity.